The Audit Committee: Management Watchdog or Personal Friend of the CEO? - Bruynseels, Liesbeth; Cardinaels, Eddy (The Accounting Review, 2014)
ABSTRACT To ensure that audit committees provide sufficient oversight over the auditing process and quality of financial reporting, legislators have imposed stricter requirements on the independence of audit committee members. Although many audit committees appear to be “fully” independent, anecdotal evidence suggests that CEOs often appoint directors from their social networks. Based on a 2004 to 2008 sample of U.S.-listed companies after the Sarbanes-Oxley Act, we find that these social ties have a negative effect on variables that proxy for oversight quality. In particular, we find that firms whose audit committees have “friendship” ties to the CEO purchase fewer audit services and engage more in earnings management. Auditors are also less likely to issue going-concern opinions or to report internal control weaknesses when friendship ties are present. On the other hand, social ties formed through “advice networks” do not seem to hamper the quality of audit committee oversight. Data Availability: All data are publicly available from sources identified in the text.